Transforming training: Evaluating the impact of training of trainers’ programs through the lens of transformational learning theory - Qasserras, Lhoussine (Edelweiss Applied Science and Technology, 2024)
This study assesses training of trainers (TOT) programs using the framework of transformational learning theory. It explores participants’ perspectives, training quality, trainer effectiveness, training philosophies, and suggestions for program improvement. A qualitative content analysis of the participant portfolios of 16 senior teachers underscores the importance of experiential learning components such as simulations and role-plays in promoting practical skills and enhancing theoretical understanding. Based on the results, we emphasize the importance of trainers possessing qualities such as empathy and respect as well as adopting a trainee-centered approach to create a transformative learning environment. We also recommend increasing program durations to facilitate deeper exploration and reflection. These insights enhance the continuing discussion on adult education and trainer development, providing recommendations for TOT programs.